Studies in law, politics, and society. Vol. 79 - Sarat, Austin (Bingley, U.K. : Emerald Publishing Limited, 2019)
This special issue of Studies in Law, Politics and Society contains two sections. In the first, 'Religious Inspirations and Legal Responses', contributors examine the interaction between law and religion. They consider the liberal tradition in which the law stands in stark opposition to religion, as well as traditions in which the law is inseparable from the sacred, revealing the complex and often controversial relationship between law and religion. Case studies include religious education, Sharia debates in Australia, Canada and the U.K., and same-sex marriage in the U.S. The second section, 'Law and Social Change: Old Questions, New Answers', examines the ways in which the law simultaneously enhances and inhibits projects of social change. The varied ways in which legal institutions respond to social movements are analyzed, along with the cultural contingencies associated with law's ability to promote change, and what we can learn about law and social change by examining societies across the globe. Case studies include refugee and asylum seeker detention and the political risks of litigation in the U.S.
Prelims -- Law and religion -- Law and social change: old questions, new answers.
Print version record.
Keywords: Religion and law; Sociological jurisprudence; Law -- Political aspects; Political sociology; Political Science -- General; Politics & government